Green Turns Grey: Green Purchase Continuity Through Protection Motivation Theory: Hijau Menjadi Abu-abu: Kontinuitas Pembelian Hijau Melalui Protection Motivation Theory - Saputri, Windy Eka (DAS Institute, 2026)
This conceptual paper extends the use of Protection Motivation Theory (PMT) to green consumer behavior while incorporating cognitive dissonance. The model implemented perceived severity, response efficacy, and green knowledge as vital predictors affecting consumers’ protective motivations for sustainable consumption. Those with a consistent green purchasing behavior are likely to see a threat to the environment as severe and believe in the effectiveness of their action. Unfortunately, greenwashing is likely to yield cognitive dissonance and demotivate the consumer. Dissonance may arise when firms' dishonest claims of social and environmental sustainability contrast with consumers' pro-environmental moral values. This dissonance may weaken the intent to continue purchasing the product, ultimately resulting in the product’s disuse, demonstrating the fragile trust consumers have in the green market. The model advocates the need for clear communication and consumer education to responsibly adopt pro-environmental behavior. This paper extends PMT beyond its conventional health domain toward sustainability and ethical marketing. On the practical side, the cultivation of sustained green consumption and the development of long-lasting consumer relationships demand real green initiatives.